2019
DOI: 10.1194/jlr.m089508
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-induced hypertriglyceridemia in rhesus macaques is attenuated with fish oil or ApoC3 RNA interference

Abstract: inhibition lowered plasma TG concentrations in animals with diet-induced hypertriglyceridemia. In summary, ApoC3 is an important independent correlate of TG-rich lipoprotein concentrations in rhesus macaques consuming a high-fructose diet. ApoC3 is a promising therapeutic target for hypertriglyceridemia in patients with MetS and diabetes.-Butler, A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Finally, we report on the effects of inhibiting hepatic ANGPTL3 expression with RNAi on plasma lipid/lipoprotein profiles. This study includes comparisons with the responses to inhibiting hepatic APOC3 concentrations, which have been reported previously (30).…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Finally, we report on the effects of inhibiting hepatic ANGPTL3 expression with RNAi on plasma lipid/lipoprotein profiles. This study includes comparisons with the responses to inhibiting hepatic APOC3 concentrations, which have been reported previously (30).…”
mentioning
confidence: 98%
“…Nonhuman primates are an important resource for the translational research of novel therapies against obesityrelated metabolic diseases (26,27). Previous studies have demonstrated that rhesus macaques provided with fructose or high-fructose corn syrup (HFCS) supplements (300-600 kcal/d) rapidly gain weight and develop features of metabolic syndrome (insulin resistance, hypertriglyceridemia, and increased APOC3) (28)(29)(30). Using this model, we recently reported that an RNAi construct targeting hepatic APOC3 expression reduces plasma TG concentrations (30).…”
mentioning
confidence: 99%
See 3 more Smart Citations